KAJIAN GENDER TENTANG PENGEMUDI GO-JEK WANITA DI KOTA MANADO - Tumimbang, Gladys N.; Suwu, Evie A. A.; Tumiwa, Juliana (Universitas Sam Ratulangi, 2020)
In today's globalization era, the rapid development of technology demands the community to follow its existing developments. In addition, the development also provides convenience to the community in assisting daily life, so that people now prefer to use practical things.With the development of online-based transportation, the fans of the work also increased, especially in large cities such as Manado. Many people who make the profession of motorbike taxi driver online as a main job or a side job. In general motorbike taxi is a job that is identical to men, but this work is also in demand by women. In addition to the increasingly high competition in the workforce and the higher level of life needs encourages women to become online motorbike taxi drivers, because being an online motorbike taxi driver requires no special skills and a high level of education.About the Presence of the female Go-Jek driver in Manado City, the community responds with different perception. Some of the people of Manado still have not received a woman's Go-Jek driver by cancel every order when she learns that she is a woman. But some of the people of Manado city especially women are very much appreciated to appreciate the work of women go-Jek drivers because they feel comfortable and more friendly when getting a woman's Go-Jek driver.Â Keywords: women, transportation, motorbike taxi online